2005
DOI: 10.1055/s-2005-872045
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum C-Reactive Protein Concentration Early in Pregnancy and Subsequent Pregnancy Loss

Abstract: The purpose of this study was to determine the relationship between maternal inflammation and first or second trimester pregnancy loss. A nested case-control analysis was performed among the cohort enrolled in the Oral Conditions and Pregnancy study. We compared maternal serum C-reactive protein concentration between women with a pregnancy loss at < 21 weeks gestation to control women without gestational diabetes or preeclampsia who delivered at term. Participants were 2:1 frequency matched to cases by materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
(12 reference statements)
0
20
0
2
Order By: Relevance
“…In addition, intentional local endometrial inflammation during blastocyst transfer following IVF has been shown to improve pregnancy outcomes [63]. Increased maternal CRP may be associated with protection from pregnancy loss, particularly in losses greater than 12 weeks gestation [64]. Thus, an inflammatory response has been suggested to be a positive signal for implantation; however, too much (or too little) inflammation may indicate pathology [62], [65].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, intentional local endometrial inflammation during blastocyst transfer following IVF has been shown to improve pregnancy outcomes [63]. Increased maternal CRP may be associated with protection from pregnancy loss, particularly in losses greater than 12 weeks gestation [64]. Thus, an inflammatory response has been suggested to be a positive signal for implantation; however, too much (or too little) inflammation may indicate pathology [62], [65].…”
Section: Introductionmentioning
confidence: 99%
“…En otros estudios se pone de manifiesto que el tratamiento y la profilaxis de la enfermedad periodontal reduce el riesgo de parto prematuro y el bajo peso al nacer (4, 21,32) y que por tanto es de gran importancia el control de la salud periodontal durante el proceso gestacional (22,(32)(33)(34).…”
Section: Controversias Entre La Enfermedad Periodontal Y Las Complicaunclassified
“…La combinación de los mediadores de la inflamación junto con el aumento de la concentración hormonal, puede llegar a constituir un factor de riesgo para la integridad de la unidad fetoplacentaria en mujeres con una respuesta inmunitaria celular reducida como consecuencia del embarazo (9,31,34).…”
unclassified
“…The authors reported that elevated fetal CRP levels at delivery were associated with higher long-term average maternal exposure to PM 10 (particulate matter ≤ 10 µm in aerodynamic diameter) and NO 2 (nitrogen dioxide). Other studies have reported that neither preeclampsia (Kristensen et al 2009) nor pregnancy loss (Boggess et al 2005) is associated with a systemic inflammation as reflected by CRP levels. However, van den Hooven et al (2012) insisted that exposure to air pollution may lead to systemic inflammation in pregnancy.…”
mentioning
confidence: 97%